Improving FRT capability and alleviating output power of DFIG wind turbine by SMES-FCL - Ngamroo, Issarachai (My University, 2016)
The fault ride through (FRT) capability, and output power fluctuation are important problems of the grid connected-doubly fed induction generator (DFIG) wind turbine. In this paper, the superconducting magnetic energy storage-fault current limiter (SMES-FCL) with the common part of superconducting coil (SC) is presented to solve both problems. During normal operation, the control of SC is employed to alleviate the output power fluctuation of DFIG. During system faults, the SC acts as the fault current limiter to augment the FRT capability. The control scheme of inverter and DC-chopper using PI controllers are described. Simulation study confirms that the SMES-FCL yields the superior stabilizing effect over the individual SMES or FCL.
Keywords: doubly fed induction generator wind turbine; fault ride through; FCL; power fluctuation; SMES